2017
DOI: 10.15419/bmrat.v4i02.150
|View full text |Cite
|
Sign up to set email alerts
|

The potential role of mesenchymal stem cells in a hypoxia model induced by sodium nitrite in testes of male albino rats

Abstract: Introduction: The present work aims to examine the possible role of stem cells on biochemical markers and histopathological alterations of hypoxia caused by sodium nitrite (NaNO 2 ) toxicity in testes of male rats. Methods: In this study, 96 adult male albino rats were divided into 6 groups (16 rats each). Group 1 (G1) was the control group and received distilled H 2 O. Group 2 (G2) received daily NaNO 2 (35 m/kg bwt/ day) via subcutaneous injection for 3 weeks. Group 3 (G3) received NaNO 2 for 2 weeks and wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 54 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…is fall in the antioxidant enzymes' activities may signify the decrease of the antioxidant activity due to the oxidative stress caused by NaNO 2 . NaNO 2 has inhibitory effects on the SOD and CAT enzymes and other antioxidant enzymes in erythrocytes [30,31]; hence, the levels of O 2 and hydrogen peroxide (H 2 O 2 ) are elevated and cause oxidative stress [7] that can destruct other biomolecules, such as protein, lipid, and DNA [7,11,30,32]. O 2 can irreversibly oxidize non-sulfur centers of the antioxidant enzymes during protein oxidation, leading to their inactivation [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…is fall in the antioxidant enzymes' activities may signify the decrease of the antioxidant activity due to the oxidative stress caused by NaNO 2 . NaNO 2 has inhibitory effects on the SOD and CAT enzymes and other antioxidant enzymes in erythrocytes [30,31]; hence, the levels of O 2 and hydrogen peroxide (H 2 O 2 ) are elevated and cause oxidative stress [7] that can destruct other biomolecules, such as protein, lipid, and DNA [7,11,30,32]. O 2 can irreversibly oxidize non-sulfur centers of the antioxidant enzymes during protein oxidation, leading to their inactivation [33].…”
Section: Discussionmentioning
confidence: 99%
“…e current study indicated an increase in peroxidation of the PUFA [20] due to oxidative stress. NaNO2 causes hypoxia and the production of free radicals [31] that target the side-chain methylene carbon of PUFA to remove a hydrogen atom from it to start a destructive chain reaction [43]. e decrease of the MDA and F2-isoprostanes in the red okra-treated mice, especially those given 100 mg/ kg BW indicated a decrease in lipid peroxidation.…”
Section: Veterinary Medicine Internationalmentioning
confidence: 99%